Ghrelin enhances gastric emptying in diabetic gastroparesis: a double blind, placebo controlled, crossover study. Issue 12 (5th August 2005) - Murray, C D R; Martin, N M; Patterson, M; Taylor, S A; Ghatei, M A; Kamm, M A; Johnston, C; Bloom, S R; Emmanuel, A V
Abstract : Background: Diabetic gastroparesis is a disabling condition with no consistently effective treatment. In animals, ghrelin increases gastric emptying and reverses postoperative ileus. We present the results of a double blind, placebo controlled, crossover study of ghrelin in gastric emptying in patients with diabetic gastroparesis. Methods: Ten insulin requiring diabetic patients (five men, six type I) referred with symptoms indicative of gastroparesis received a two hour infusion of either ghrelin (5 pmol/kg/min) or saline on two occasions. Blood glucose was controlled by euglycaemic clamp. Gastric emptying rate (GER) was calculated by real time ultrasound following a test meal. Blood was sampled for ghrelin, growth hormone (GH), and pancreatic polypeptide (PP) levels. Cardiovagal neuropathy was assessed using the Mayo Clinic composite autonomic severity score (range 0 (normal)–3). Results: Baseline ghrelin levels were mean 445 (SEM 36) pmol/l. Ghrelin infusion achieved a peak plasma level of 2786 (188) pmol/l at 90 minutes, corresponding to a peak GH of 70.9 (19.8) pmol/l. Ghrelin increased gastric emptying in seven of 10 patients (30 (6)% to 43 (5)%; p = 0.04). Impaired cardiovagal tone correlated inversely with peak postprandial PP values (p<0.05) but did not correlate with GER. Conclusions: Ghrelin increases gastric emptying in patients with diabetic gastroparesis. This is independent of vagal tone. We propose that analogues of ghrelin may represent a new class of prokinetic agents.